Cardiovascular System of Agouti (Dasyprocta prymnolopha) - Cavalcante, Maria Michele Araújo de Sousa; Fonseca, Clarisse Maria Barbosa; Silva, Andrezza Braga Soares; Mendonça, Tarsia Giabardo Silva; Guerra, Sérgio Paulo Lima; Viana, Felipe José Costa; Fortes, Eunice Anita Moura; Carvalho, Maria Acelina Martins; Conde Júnior, Aírton Mendes (Acta Scientiae Veterinariae, 2022)
Background: The species Dasyprocta prymnolopha is a wild rodent with a geographic distribution that extends from Mexico to South America, including Brazil. Agouti has been the subject of morphophysiological research, but data on the cardiovascular system remains limited. Therefore, the objective was to describe the macroscopic and microscopic morphology, including the study of the cardiac and coronary system syntopy of the species D. prymnolopha. Materials, Methods & Results: Twelve Dasyprocta primnolopha adults were used, 6 males and 6 females. Topographic analysis of the heart was evaluated in situ, with subsequent measurement, anatomovascular description and macroscopic study of cardiac and coronary vascularization. A microscopic investigation and identification of structural cardiac aspects were also carried out in adult agoutis, the biological samples of the heart were submitted to histological techniques and stained with Hematoxylin and Eosin and Masson’s Trichrome. The heart is located between the end of the 2nd and the beginning of the 5th intercostal space, with the apex reaching the 6th space. It presents the presence of 2 ligaments: phrenopericardium and sternopericardium. The right atrioventricular valve is composed of 2 cusps, the parietal and the septal, with variations within the same species for 3 cusps. Projections that interconnect the papillary muscles with each other were observed. In the left ventricle there are variations in the number of papillary muscles (range 2 to 4). In the region of the aortic valve, 5 ostia were observed in the left aortic sinus in all animals. The coronary circulation has a predominantly left distribution. Histologically, the heart consists of 3 main layers: endocardium, myocardium, and epicardium. The cusp valves of the atrioventricular openings are composed of endocardial folds that contain a central plate of dense connective tissue, and inserted in this cardiac musculature was observed the cardiac skeleton, with its fibrous ring consisting of collagen and elastic fibers that surrounds the atrioventricular opening. Discussion: Cardiac assessment in wild animals is challenging, as in-depth knowledge of the morphology of the cardiovascular system is required for the use of diagnostic tools. In this first anatomical study of the heart, this organ presents syntopy with those of other rodents, but the topography may vary in individuals of the same species, which may be related to the accentuated vertebral curve. The phrenopericardial and sternopericardial ligaments were observed in this research, although there are no reports in other species of Dasyprocta sp. The arrangement of the arteries has, as a particularity, the larger left atrium in relation to the heart/atrium size ratio when compared to other domestic species, covering the left coronary sinus until it reaches the left atrial surface. In the agouti, it was observed that the vascularization is left, with the left coronary artery giving rise to both the paraconal and subsinuous interventricular branch, a fact found in animals such as ruminants, dogs. In the histological observations of the present study, the heart was similar to that of other mammals. Our data reveal morphological characteristics similar to those of other mammals, but with very expressive characteristics that differ even within the species. It is important to generate new information to elucidate cardiac and coronary diagnostic analyses, which can be extended to different species. Keywords: agouti, wild rodent, coronary arteries, cardiac, heart, histology, morphology.